2004
DOI: 10.1081/ja-120038030
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and Ethnic Identity as Predictors of Drug Norms and Drug Use Among Preadolescents in the US Southwest

Abstract: This article reports the results of research exploring how ethnicity and ethnic identity may "protect" adolescents against drug use and help them form antidrug use norms. This study was conducted in 1998 and is based on a sample of 4364 mostly Mexican American seventh graders residing in a large southwestern city of diverse acculturation statuses. It aims at testing existing findings by conducting the research within the unique geographic and ethnic context of the Southwest region of the United States. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
105
4
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(119 citation statements)
references
References 53 publications
7
105
4
3
Order By: Relevance
“…Los inmigrantes de segunda generación tienden a imitar los valores de los autóc-tonos al haber asimilado sus valores y costumbres (Marsiglia et al, 2004). Algunos autores han señalado el denominado como efecto «White male» (Bachman et al, 2011), refiriéndose al mayor riesgo de éstos en el consumo de sustancias.…”
Section: Discussionunclassified
“…Los inmigrantes de segunda generación tienden a imitar los valores de los autóc-tonos al haber asimilado sus valores y costumbres (Marsiglia et al, 2004). Algunos autores han señalado el denominado como efecto «White male» (Bachman et al, 2011), refiriéndose al mayor riesgo de éstos en el consumo de sustancias.…”
Section: Discussionunclassified
“…These findings are in line with studies that have examined the concentration of ethnic-minority students in school settings (school ethnic density). Those studies report that higher school ethnic density is associated with improved mental health (Georgiades et al, 2013;Gieling et al, 2010) and reduced substance use (F. F. Marsiglia et al, 2004) among ethnic-minority pupils. Studies of ethnic density among ethnic-minority adults have also shown that people living among a greater proportion of M A N U S C R I P T…”
Section: Discussionmentioning
confidence: 99%
“…With regards to individual dimensions of ethnic identity and with pooled ethnically diverse samples, research has found ethnic identity affirmation to be associated with lower levels of drug use (Marsiglia, Kulis, & Hect, 2001;Marsiglia, Kulis, Hect, & Sills, 2004). These results support the assertion that ethnic identity exploration and commitment to be positively associated with self-esteem in pooled ethnically diverse samples (Umaña-Taylor, Yazedjian, & Bámaca-Gómez 2004, 2009).…”
Section: Ethnic Identity and Psychosocial Functioningsupporting
confidence: 78%
“…Studies conducted with late Hispanic adolescents have paralleled these findings, detecting a positive relationship between ethnic identity and self-esteem (Bracey, Bamaca-Gomez, & Umaña-Taylor, 2004;Umaña-Taylor, 2004). In stark contrast, ethnic identity has also been found to be positively associated with heavy alcohol use in Mexican-American College Students (Zamoanga, Raffaelli, & Horton, 2006), and with alcohol use in early Hispanic adolescents (Marsiglia, Kulis, Hect, & Sills, 2004 -Taylor & Shin, 2007). However , French, Kim, and Pillado (2006) found ethnic identity exploration to be positively associated with delinquency.…”
Section: Ethnic Identity and Psychosocial Functioningmentioning
confidence: 70%